Thrombotic thrombocytopenic pupura (TTP) dinner symposium proceedings. Issue 8 (2nd August 2016) - Pavenski, Katerina; Cataland, Spero; Kremer Hovinga, Johanna; Thomas, Mari; Vanhoorelbeke, Karen
ABSTRACT: Answering TTP was established to engage the thrombotic thrombocytopenic purpura (TTP) community to further the common goals of patient support, education of patients and medical professionals, and the funding of research to improve the treatment and care of TTP patients. Answering TTP convened a dinner symposium on 23 June 2015 in Toronto, Canada during the International Society of Thrombosis and Haemostasis (ISTH) Congress to bring TTP clinicians and research together to highlight the key clinical and research questions in the field. These questions are increasingly important given the recent advances and novel therapies that have or will soon enter clinical study for patients with TTP.